2017
DOI: 10.1002/da.22709
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia is associated with suicidal ideation independently of depression: A meta-analysis

Abstract: Our major finding is the robust association between anhedonia and current suicidal ideation, independently of depression. This is highly relevant for the clinicians' daily practice and might help improving suicidal risk detection and the development of new therapeutic strategies for suicide prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
91
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 187 publications
(112 citation statements)
references
References 60 publications
18
91
0
3
Order By: Relevance
“…Anhedonia has been found to be predictive of future suicidal thoughts, attempts, and behavior (Ballard et al, ; Spijker et al, ; Winer et al, ). A recent meta‐analysis found that anhedonia was significantly related to current suicidal ideation, even while controlling for depression and other psychiatric diagnoses (Ducasse et al, b). Though many previous accounts report the effect of high levels of chronic anhedonia, our recent research suggests that it is acute anhedonia, rather than chronic, that is prospectively predictive of suicide (Hawes et al, ).…”
Section: Suicide Crisis Syndromementioning
confidence: 99%
“…Anhedonia has been found to be predictive of future suicidal thoughts, attempts, and behavior (Ballard et al, ; Spijker et al, ; Winer et al, ). A recent meta‐analysis found that anhedonia was significantly related to current suicidal ideation, even while controlling for depression and other psychiatric diagnoses (Ducasse et al, b). Though many previous accounts report the effect of high levels of chronic anhedonia, our recent research suggests that it is acute anhedonia, rather than chronic, that is prospectively predictive of suicide (Hawes et al, ).…”
Section: Suicide Crisis Syndromementioning
confidence: 99%
“…Consistent with prior studies, higher State‐A was associated with greater depressive symptoms, whereas trait anticipatory and consummatory anhedonia both were not significantly associated with depression (Gard et al, ; Loas et al, ). Some studies found that State‐A (recent changes and acuity) was especially predictive of suicidal ideation independently of depressive symptoms (Ducasse et al, ; Hawes et al, ; Winer et al, ; Winer et al, ). Other studies found that State‐A mediated the positive association between depressive symptoms/perceived burdensomeness/thwarted belongingness and suicidality (Loas et al, ; Zielinski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Anhedonia, defined as a lowered ability to experience pleasure, has been identified as a suicide risk factor (Loas, ). Recent works suggested taking into account the severity and the type of anhedonia when examining suicidal ideation (SI) (Ducasse et al, ; Loas et al, ). Anhedonia has been defined as both a state and a trait, dependent on whether it is thought of as an aspect of a depressive state or a personality trait (Loas & Pierson, ).…”
mentioning
confidence: 99%
See 2 more Smart Citations